Case Report: Comprehensive Management Of Patients With Lung Cancer Suspected Of Brain Metastases Accompanied By Pneumonia - Mustofa, Syazili; Nursidiq, Iqbal Muhammad Rafi; Yuningrum, Hesti; Busman, Hendri; NA, Ahmad Mufid (Jurnal Ilmu Kedokteran dan Kesehatan, 2024)
Worldwide, the most frequently diagnosed cancer is lung cancer. The chief complaints of the disease are dyspnea and chest discomfort. Lung cancer causes an immunodeficiency state in the body, which can lead to infection. Lung cancer is also known to complicate cerebrovascular disease, causing an infarction or stroke. This case report aims to elucidate the etiology of lung cancer-associated infection and cerebrovascular disease and effectively detect and heal the disease. A 58-year-old man came with his family to the emergency department of Abdoel Moeloek Hospital, Lampung Province with complaints of shortness of breath that worsened, accompanied by complaints of cough and pain in the right chest. The doctor conducted a detailed examination and then the doctor diagnosed the patient with community-acquired pneumonia because of immunodeficiency from lung squamous cell carcinoma, hemiparesis dextra, dysarthria due to cerebrovascular disease, and malnutrition. The doctor administered oxygen and a nebulizer to the patient. Subsequently, he was hospitalized for symptomatic therapy and antibiotic treatment.